2019
DOI: 10.3390/ijerph16050892
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Industry CSR Organisations: What Can Their Twitter Activity Tell Us about Their Independence and Their Priorities? A Comparative Analysis

Abstract: There are concerns about the accuracy of the health information provided by alcohol industry (AI)-funded organisations and about their independence. We conducted a content analysis of the health information disseminated by AI-funded organisations through Twitter, compared with non-AI-funded charities, to assess whether their messages align with industry and/or public health objectives. We compared all tweets from 2016 from Drinkaware (UK); Drinkaware.ie (Ireland); and DrinkWise (Australia), to non-AI-funded ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 45 publications
(64 reference statements)
2
41
0
Order By: Relevance
“…11 These organisations have been repeatedly shown to align themselves with the economic interests of the AI rather than acting as independent bodies. 11,12 Petticrew et al describe three strategies employed by the AI that share strong similarities to those used by tobacco companies when disseminating information about cancer: denying, omitting or disputing the evidence that alcohol consumption increases cancer risk; mentioning cancer, but misrepresenting or obfuscating the nature or size of that risk; and focusing discussion away from the independent effects of alcohol on common cancers. 13 Concerningly, 24 out of 26 websites from AI-related bodies contained significant omissions or misinformation.…”
Section: Exploring the Gap In The Public's Understanding Of The Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…11 These organisations have been repeatedly shown to align themselves with the economic interests of the AI rather than acting as independent bodies. 11,12 Petticrew et al describe three strategies employed by the AI that share strong similarities to those used by tobacco companies when disseminating information about cancer: denying, omitting or disputing the evidence that alcohol consumption increases cancer risk; mentioning cancer, but misrepresenting or obfuscating the nature or size of that risk; and focusing discussion away from the independent effects of alcohol on common cancers. 13 Concerningly, 24 out of 26 websites from AI-related bodies contained significant omissions or misinformation.…”
Section: Exploring the Gap In The Public's Understanding Of The Linksmentioning
confidence: 99%
“…13 A comparative analysis of twitter feeds from industry funded and non-industry funded charities revealed similar findings, with the AI instead focusing on the behavioural aspects of drinking. 12 Both the AI and its related bodies have dismissed or disputed the evidence behind the UK 2016 low-risk drinking guidelines, including those that state 'the risk of developing cancers … increase with any amount you drink on a regular basis.' The Portman Group's reply to the public consultation clearly misrepresents the cancer risk associated with drinking, for example stating that alcohol increases 'the risk of a small number of cancer types', distracting attention away from the number of individuals affected by these cancers.…”
Section: Exploring the Gap In The Public's Understanding Of The Linksmentioning
confidence: 99%
“…For the alcohol industry, there is evidence of the use of similar strategies to influence policy, research, and practice [11,14]. Also described in the literature is the creation and dissemination of misleading information related to health risks associated with alcohol consumption, especially the increased risk of cancer [15,16], and a focus on the health benefits of alcohol intake [11,15,16]. Hessari et al provide evidence of a shift away from the harm associated with alcohol drinking for women, in particular breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…The five papers which included a focus on alcohol and advertising industry practices [9,10,13,14,16] add to a growing evidence base about such practices. For example, Knai et al [9] found that both the production and uptake of responsibility pledges by responsibility deal partners in the UK, including organisations with commercial interests, were largely driven by the interests of partners themselves, and this made it possible for them to resist change.…”
mentioning
confidence: 99%
“…A somewhat similar finding emerged in a study conducted in Lebanon [13], where it was noted that industry representatives argued against evidence-based policies in reducing alcohol harm experienced by youth. A study by Hessari and colleagues [10] found that alcohol industry funded organisations were significantly more likely to tweet about behavioural aspects of drinking and less likely to mention (breast) cancer risk [10]. A second study by Hessari et al involved a review of 39 case studies published by the advertising industry evaluating the effect of alcohol advertising campaigns [14].…”
mentioning
confidence: 99%